Centrifuge modeling of single pile-shallow foundation interaction in reverse fault. Issue 141 (February 2021) - Yao, Chaofan; Takemura, Jiro; Zhang, Junchen
Abstract: Both pile foundations and shallow foundations are deemed to be vulnerable to significant fault deformation. However, the pile foundation-shallow foundation interaction in dip-slip fault has never been studied, to the authors' knowledge. This study presents the results of two centrifuge tests, in which a shallow foundation and single piles are subjected to reverse faulting. The tests are compared with the ones from previous studies in the following conditions: free-field, with only a shallow foundation, and with only single piles. The results show that there is a significant interaction between the single piles and shallow foundations. The presence of single piles leads to larger displacements and rotations of shallow foundations. The shallow foundation affects the pile behaviors in two ways: 1) the rupture diversion caused by the shallow foundation leads to different magnitudes and distributions of soil displacements along the piles; 2) the shallow foundation prevents the free deformation of soil, resulting in increasing soil stress even after outcropping. Highlights: There is significant interaction of piles and shallow foundations in revere fault. The piles lead to larger displacements and rotations of shallow foundations. The shallow foundation results in different soil displacement distributions. The shallow foundation causes soil stress increasing even after outcropping.